2018
DOI: 10.1159/000493573
|View full text |Cite
|
Sign up to set email alerts
|

Liver Maximum Capacity: A Novel Test to Accurately Diagnose Different Stages of Liver Fibrosis

Abstract: Aim: To assess the diagnostic accuracy of liver maximum capacity (LiMAx®) test compared to transient elastography (TE) and serum biomarkers for the noninvasive detection of different stages of liver fibrosis and cirrhosis. Patients and Methods: We retrospectively correlated LiMAx®, TE, aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio (AAR), AST-to-platelet ratio index (APRI), and fibrosis-4 (FIB-4) score with histological specimens in 102 patients with chronic liver disease (CLD) who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…However, both methods were limited in separating patients with no fibrosis from those with moderate fibrosis unlike reported for a cohort of obese adolescents with pediatric nonalcoholic fatty liver disease. 24 The ability of the LiMAx test to accurately diagnose different stages of liver fibrosis has recently been presented by Buechter et al 26 In their retrospective analysis of 102 patients with CLD, similar to our findings, clear decreasing tendencies of LiMAx values with increasing histological degrees of fibrosis, according to the Desmet & Scheuer scoring system, were observed. Furthermore, their AUROC analysis revealed that the LiMAx discriminated best between mild to moderate fibrosis (Desmet F0-3) and cirrhosis (Desmet F4) but less accurate between no and moderate fibrosis stages.…”
Section: Discussionsupporting
confidence: 90%
“…However, both methods were limited in separating patients with no fibrosis from those with moderate fibrosis unlike reported for a cohort of obese adolescents with pediatric nonalcoholic fatty liver disease. 24 The ability of the LiMAx test to accurately diagnose different stages of liver fibrosis has recently been presented by Buechter et al 26 In their retrospective analysis of 102 patients with CLD, similar to our findings, clear decreasing tendencies of LiMAx values with increasing histological degrees of fibrosis, according to the Desmet & Scheuer scoring system, were observed. Furthermore, their AUROC analysis revealed that the LiMAx discriminated best between mild to moderate fibrosis (Desmet F0-3) and cirrhosis (Desmet F4) but less accurate between no and moderate fibrosis stages.…”
Section: Discussionsupporting
confidence: 90%
“…The superiority of LiMAx, however, is not essentially surprising: the applied substrate ( 13 C-methacetin) is metabolized by the cytochrome P450 1A2 enzyme - which is expressed in hepatocytes exclusively. In a recently published work of our group, we could demonstrate that structural changes in the course of CLD (reflected by different fibrosis-stages) were closely associated with changes of enzymatic liver function measured by LiMAx (Spearman’s r −0.68) 13 . In contrast, routine laboratory parameters - used for the calculation of above-mentioned serum indices - are not liver-specific and released in various organs of the human body.…”
Section: Discussionmentioning
confidence: 78%
“…Subsequently, our results and claims have to be interpreted with caution and warrant further validations by other groups. However, LiMAx has been shown to correlate well with histological changes in different stages of liver fibrosis and cirrhosis in chronic liver disease [45]. Despite being certainly different in pathogenesis to other more common causes of chronic liver disease, it is assumable that LiMAx might also be associated with the histological patterns of IFALD.…”
Section: Discussionmentioning
confidence: 99%
“…Data presented as mean ± standard deviation. SBS-QoL, Short Bowel Syndrome-Quality of Life.The SF-36 Physical Component Summary (PCS) showed a significant improvement in quality of life from baseline to 6 months (29(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) vs. 39(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46); 0.002), stayed constant between the 6 and 12 month time points(39 (31-46) vs. 36(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46); p = 0.069) and slightly improved between 12 and 24 months (36(30)(31)(32)(33)(34)(35)...…”
mentioning
confidence: 99%